The Effects of the Insurance Market in the Development of Western Balkans Countries, with Special Emphasis on Kosovo - Kukaj, Halil; Morina, Fisnik; Misiri, Valdrin (European Journal of Sustainable Development, 2019)
The purpose of this research is to see whether the insurance influences the economic development of Western Balkan countries. Currently, insurance comprises an economic sector that includes all activities of conception, production and trading of this type of service that is of public interest but generally carried out by private law entities. For the specification of the econometric model in this research, we are based on the secondary data published in the official reports of the World Bank, the Central Bank, and the statistical agencies of some countries. To measure empirical results, there are used these statistical tests: fixed effects model, Hausman Taylor Regression, generalized method of the moment (GMM), and GLS regression. Based on the empirical results, we can conclude that life insurance and non-life insurance have a significant connection and positively impact the economic growth of these countries. Other variables that have shown a positive result in economic growth are: GDP per capita, Exports, whereas variables that negatively impact on economic growth are inflation and government spending. The empirical results of this document may recommend that relevant institutions implement institutional improvements that contribute to strengthening competition, advancing risk management techniques, and so on. In conclusion, we can say that future researches can be done as events, life insurance or non-life insurance impact on economic growth in Kosovo and in the countries of the region. The study is carried out with secondary data, and all empirical analyses are original. Through the results of this study we intend to offer more empirical evidence for our country and countries in the region recommending that relevant institutions improve the functioning of the financial sector and especially the insurances part because it is the factor that affects the economic growth. Key words: Economic growth, life insurance, non-life insurance, Kosovo. JEL Classification: C23, E31, G22, O11